METODE TALKING STICK DENGAN MEDIA AUDIO UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN STENOGRAFI - Utami, Wahyuni Sri (Fakultas Ekonomi, Universitas Negeri Semarang, 2013)
Stenography learning in class X Office Administration 3 at SMK Negeri 1Pemalang indicated the low learning motivation. The purpose of this research was toknow the studentsâ learning motivation improvement after using talking stick methodwith audio media at Stenography subject in class X Office Administration at SMK N 1Pemalang. It was a classroom action research conducted in three cycles which eachcycle was consisted of planning, implementation, observation, and reflection. The datawere collected by observation and test. Then, the data were analyzed by percentagedescriptive. The results showed that talking stick method with audio media can improvestudents motivation at Stenography subject in class X Office Administration 3 at SMKN 1 Pemalang. The average of studentsâ motivation on the first cycle was 63.08%, thenincreased up to 72.08% on the second cycle and finally, it went up to 85.08% on thethird cycle.